Language Policies in STEM Subjects: Triggering Inclusion, Exclusion, or Abjection? - Andersen, Katja N.; Bagger, Anette (Discourse and Communication for Sustainable Education, 2023)
The combination of language policies, the global testing industry, and the role of STEM subjects in school systems have been shown to undermine the inclusion of all pupils, especially with regard to language backgrounds. This lack of inclusion shows signs of developing into a point of systematic exclusion for those students. In this article we will consider the language policies in two national contexts, the Swedish and the Luxembourgish ones, and specifically examine issues of in(ex)clusion in relation to multi-lingualism in STEM teaching. This study analyzes policy documents on (1) inclusion, (2) language use, and (3) STEM teaching at school in the two national contexts, using a methodology that builds on Popkewitz’s (2013; 2014) approach to politics of schooling. Our results show, first, that different policies on language and multilingualism become visible in policy documents for primary school teaching in Sweden and Luxembourg. Secondly, this article discusses what impacts these policies may have on matters of inclusion, exclusion, or abjection in STEM teaching contexts at primary schools.